'Choose, collect, manage, win!': Neoliberalism, enterprising culture and risk society in video game covers. (December 2018) - Oliva, Mercè; Pérez-Latorre, Óliver; Besalú, Reinald
This article aims to identify the relationship between video games and neoliberal values. To fulfil this aim, it analyses the covers of the 20 top-selling video games in the United States each year from 2010 to 2014 (a total of 80 different games). Video game covers are a type of paratext, that is, texts that accompany another text to promote it and to guide its reading. Thus, video game covers choose and highlight some of the games' features over others, and by doing that they construct a discourse. In this article, it is argued that regardless of genre, the covers analysed convey and promote neoliberal values, such as freedom and choice, entrepreneurship, consumption and accumulation of goods, customization, novelty, individualism and meritocracy. This promotion of neoliberal values is combined with an appeal to the concerns of 'risk society'. Thus, the covers of the top-selling video games play on fears linked to the new context created by the economic crisis while at the same time legitimizing the neoliberal ideal of the 'enterprising self' as a model for dealing with it.